Production method of environment-friendly light calcium silicate board

By using fly ash, cement and other raw materials, combined with surface modified bamboo fibers and inorganic modified fillers, environmentally friendly lightweight calcium silicate boards are prepared, which solves the problems of insufficient strength and poor environmental performance of traditional calcium silicate boards, and achieves a comprehensive effect of high strength, light weight and environmental protection.

CN119638293AActive Publication Date: 2025-03-18SHANDONG LIANYINSHAN ENVIRONMENTAL PROTECTION BUILDING MATERIALS CO LTD

Patent Information

Application Number
CN202411894538.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Traditional calcium silicate boards have shortcomings in improving strength, especially in special areas such as tunnels and subway projects, which cannot be met. At the same time, the asbestos fibers used in traditional calcium silicate boards are harmful to human health.

Method used

Fly ash, cement, slurry lime, reinforced components and inorganic modified fillers are used as the main raw materials, and environmentally friendly lightweight calcium silicate plates are prepared through stirring and cold press pressing. The reinforcement components are grafted with bamboo fibers of 1-naphthol-3,6-disulfonate through surface grafting. The modified bamboo fibers are closely combined with cement particles to improve the flexural strength of the calcium silicate plate. The inorganic modified filler is modified by the intercalation of cumulative stone to increase the layer spacing and improve the hydration and density of the slurry.

Benefits of technology

It significantly improves the strength and compactness of calcium silicate boards, extends service life, and has the advantages of lightweight and environmental protection, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638293A_ABST
    Figure CN119638293A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of calcium silicate boards, and discloses a production method of an environment-friendly light calcium silicate board, the calcium silicate board comprises the following raw materials: fly ash, cement, slaked lime, a reinforcing component, an inorganic modified filler and water; wherein the reinforcing component is bamboo fiber of which the surface is grafted with 1-naphthol-3, 6-sodium disulfonate, and the breaking strength of the calcium silicate board can be effectively improved by utilizing the bamboo fiber and sulfonic acid groups in the reinforcing component; according to the inorganic modified filler, a polymer with a large amount of quaternary ammonium salt and carboxyl groups is inserted between layers of rectorite, so that the compactness of the calcium silicate board is enhanced, and the strength of the calcium silicate board is further improved. Through the synergistic effect of the raw materials, the strength of the calcium silicate board is remarkably improved, so that the service life of the calcium silicate board is prolonged, and the application effect of the calcium silicate board in various fields is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium silicate boards, and in particular to a production method of an environmentally friendly lightweight calcium silicate board. Background Art

[0002] Calcium silicate board is a lightweight board made of siliceous materials, calcium materials, reinforcing fibers, etc. as the main raw materials, through pulping, molding, pre-curing, autoclave curing, drying and other processes. It has excellent properties such as moisture-proof, moth-proof, fire-proof, sound-proof, and strong processability. It is widely used in suspended ceilings, walls, floors, furniture, ship compartments, composite wall panels and other fields.

[0003] With the continuous advancement of science and technology and the continuous expansion of application fields, traditional calcium silicate boards can no longer meet the diversified and high value-added market demands. Therefore, improving the performance of calcium silicate boards has become an important trend in the development of the industry. In order to increase the strength of calcium silicate boards, the conventional method is to add reinforcing materials, and reinforcing fibers are the main reinforcing materials for calcium silicate boards. Traditional calcium silicate boards contain asbestos fibers in the production raw materials, which are not good for human health and may cause health problems such as cancer. Compared with traditional calcium silicate boards, ordinary calcium silicate boards have better environmental performance, but ordinary calcium silicate boards mostly use pulp as reinforcing fibers, but pulp has limited effect on the strength of calcium silicate boards and cannot meet the use requirements of special fields (such as tunnels, subway projects, etc.). Therefore, it is of great practical significance to prepare an environmentally friendly, lightweight and high-strength calcium silicate board.

[0004] In the prior art, optimizing the basic material is one of the main ways to improve the strength of calcium silicate board. For example, the invention patent with publication number CN117263634B discloses a method for preparing calcium silicate board and calcium silicate. The invention uses lime slag, fly ash, and water reducer as slurry A, and waste rubber, coal gangue, fiber, and grinding aid as slurry B. Adding waste rubber and coal gangue as components of the slurry can significantly improve the strength of the calcium silicate board. The grinding aid is triisopropanolamine, disodium hydroxyethylidene diphosphonate, and polyacrylate, which makes the grinding of slurry B more uniform, reduces the crack rate of the calcium silicate board, and further improves the strength of the calcium silicate board. The fiber is a combination of polyethylene fiber and aramid fiber, which further improves the strength of the calcium silicate board. Therefore, the calcium silicate board can be modified by preparing a filling component with high strength to obtain a high-strength calcium silicate board. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a production method of an environmentally friendly lightweight calcium silicate board.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for producing an environmentally friendly lightweight calcium silicate board, the calcium silicate board comprising the following raw materials in parts by weight: 40 to 60 parts of fly ash, 30 to 50 parts of cement, 4 to 6 parts of slaked lime, 8 to 10 parts of reinforcing components, 5 to 7 parts of inorganic modified fillers, and 100 to 200 parts of water; The production method comprises the following steps: (1) Fly ash, cement, slaked lime, reinforcing components, inorganic modified fillers and water are mixed and stirred at a stirring rate of 600 to 800 r / min for 4 to 8 hours to obtain a mixed slurry; (2) Pour the mixed slurry into the template, and then use a cold press to apply a pressure of 20 to 40 MPa for pressing. The pressing process keeps the pressure constant and lasts for 30 to 50 minutes to ensure that the slurry is fully solidified. After demolding, the blank plate is obtained; (3) Cutting the blank into products of required specifications, and then performing pre-curing, autoclaving and drying treatments to obtain an environmentally friendly lightweight calcium silicate board.

[0007] Furthermore, in step (3), the pre-curing process is: pre-curing treatment for 10 to 20 hours in an environment with a pre-curing temperature of 50 to 60° C. and a humidity of 60 to 80%.

[0008] Furthermore, the preparation method of the reinforcing component comprises the following steps: A1: placing the bamboo fiber in a potassium hydroxide solution, shaking it for 1 to 2 hours at a temperature of 40 to 50°C and a rotation speed of 100 to 200 r / min, and washing and drying the solution to obtain alkalized bamboo fiber; A2: adding alkalized bamboo fiber and N-methylpyrrolidone into a reactor, ultrasonicating to form a uniform suspension, passing nitrogen, exhausting the air, and then adding bromoacetic acid and a catalyst into the suspension, raising the system temperature to 105-115° C. under stirring conditions, and heat preservation treatment for 3-5 hours, allowing the material to cool naturally, centrifugally separating the solid material, washing the solid material, and vacuum drying to obtain modified bamboo fiber; A3: Add the modified bamboo fiber and dimethyl sulfoxide solution into a nitrogen-protected reactor, stir evenly with a magnetic stirrer, continue to add sodium 1-naphthol-3,6-disulfonate and accelerator into the reactor, stir evenly, raise the system temperature to 70-80°C, keep stirring for 4-6 hours, discharge, wash and dry to obtain the reinforcing component.

[0009] Furthermore, in step A1, the mass fraction of the potassium hydroxide solution is 10% to 40%.

[0010] Furthermore, in step A2, the catalyst is any one of tetraethyl titanate, tetrabutyl titanate or tetraisopropyl titanate.

[0011] Furthermore, in step A3, the promoter is any one of sodium carbonate, potassium carbonate or sodium bicarbonate.

[0012] Furthermore, the preparation method of the inorganic modified filler comprises the following steps: AA1: Under nitrogen protection, add N,N,N',N'-tetramethylethylenediamine to N,N-dimethylformamide, ultrasonically disperse for 15-25 minutes, then add chlorine source, after the addition, turn on the heating, wait until the system temperature reaches 60-70°C, stir at constant temperature for 4-8 hours, cool down and discharge, and the intermediate material can be obtained; AA2: Ultrasonic disperse the rectorite in deionized water to form a dispersion, add the intermediate material to the dispersion, stir for 2 to 6 hours at a temperature of 65 to 75°C, filter the material, take a solid sample, wash the sample with deionized water, and dry it to obtain an inorganic modified filler.

[0013] Furthermore, in step AA1, the chlorine is any one of 2,6-dichlorobenzoic acid or dichloroacetic acid.

[0014] Furthermore, in step AA2, the average particle size of the rectorite is 5 μm.

[0015] Beneficial effects of the present invention: (1) The calcium silicate board prepared by the present invention uses fly ash, cement, slaked lime, reinforcing components and inorganic modified fillers as main raw materials. Through the synergistic effect of various raw materials, the strength of the calcium silicate board is significantly improved, thereby extending the service life of the calcium silicate board. In addition, the calcium silicate board has the advantages of being lightweight and environmentally friendly, and has broad application prospects.

[0016] (2) The reinforcing component prepared by the present invention is bamboo fiber with 1-naphthol-3,6-disulfonic acid sodium grafted on the surface. On the one hand, bamboo fiber is used to replace traditional asbestos fiber, which is non-toxic, friendly to the human body and the environment, and has the characteristics of high strength, which can effectively improve the strength of the calcium silicate board. On the other hand, the sulfonic acid group contained in the structure of the reinforcing component can react with the calcium hydroxide in the mixed slurry, so that the cement particles are tightly adsorbed on the surface of the bamboo fiber, thereby increasing the adhesion between the reinforcing component and the mixed slurry, improving the microstructure of the mixed slurry, and enabling the reinforcing component to better compensate for the hydration network defects of the mixed slurry, thereby further improving the flexural strength of the calcium silicate board. In addition, the sulfonic acid group, due to its hydrophilic nature, can effectively absorb and retain a large amount of water in the slurry, which can not only improve the water retention capacity of the slurry, but also slow down the hydration rate of the slurry, thereby preventing the calcium silicate board from having problems such as strength reduction and cracking due to the too fast hydration process.

[0017] (3) The present invention prepares an inorganic modified filler by using rectorite as a matrix. Since rectorite has a layered structure, after intercalation modification, the interlayer spacing of the rectorite increases, and the water absorption rate increases, which is beneficial to the internal hydration of the slurry, and enhances the compactness of the calcium silicate board, thereby enhancing the compressive strength of the calcium silicate board. Among them, a large number of carboxyl groups contained in the inorganic modified filler can react with the calcium ions in the slurry to generate insoluble calcium salts, delay the hydration degree of the slurry, and improve the density of the calcium silicate board. In addition, the quaternary ammonium ions in the inorganic modified filler can exchange with the calcium ions in the slurry, significantly improving the fluidity of the slurry, being able to better fill the gaps, reducing the frequency of voids in the slurry, and producing a synergistic effect with the carboxyl group to jointly enhance the strength of the calcium silicate board.

[0018] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0020] Figure 1 This is an infrared spectrum test chart of the enhanced component prepared by the present invention.

[0021] Figure 2 This is an infrared spectrum test chart of the inorganic modified filler prepared by the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1.

[0024] 1. Preparation of reinforcing components A1: 5g of bamboo fiber was placed in a 10% potassium hydroxide solution, and the solution was shaken at 45°C and 150r / min for 1.5h. After washing and drying, alkalized bamboo fiber was obtained. A2: 5 g of alkalized bamboo fiber and N-methylpyrrolidone were added to the reactor, and ultrasonic treatment was performed to form a uniform suspension. After nitrogen was passed and the air was exhausted, 1.2 g of bromoacetic acid and 0.08 g of tetraethyl titanate were added to the suspension. The system temperature was raised to 110° C. under stirring conditions, and the temperature was kept for 4 h. After the material was naturally cooled, the solid material was separated by centrifugation, the solid material was washed, and vacuum dried to obtain modified bamboo fiber; A3: Add 5g of modified bamboo fiber and dimethyl sulfoxide solution into a nitrogen-protected reactor, stir evenly with a magnetic stirrer, continue to add 1.6g of 1-naphthol-3,6-disulfonic acid sodium and 0.1 potassium carbonate into the reactor, stir evenly, raise the system temperature to 75°C, keep stirring for 5h, discharge, wash and dry to obtain the reinforcing component.

[0025] The enhanced components were analyzed by infrared spectroscopy using a Nicolet 170sx Fourier transform infrared spectrometer. Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of the enhanced component, 1741cm -1 The characteristic absorption peak of the ester group C=O appears at 1079cm -1 The characteristic absorption peak of ether bond COC appears at 1281 cm -1 and 1038cm -1 The characteristic absorption peak of sulfonic acid group appears at

[0026] Technical principle: In the reinforcing component, first, the bamboo fiber is pre-treated with alkalization to remove lipid substances attached to its surface to obtain alkalized bamboo fiber; secondly, under the action of tetraethyl titanate, the hydroxyl groups on the surface of the alkalized bamboo fiber are esterified with the carboxyl groups in the bromoacetic acid structure to modify the halogen functional groups on the surface of the bamboo fiber to obtain modified bamboo fiber; then, under the action of potassium carbonate, the halogen functional groups on the surface of the modified bamboo fiber and the hydroxyl groups in the structure of 1-naphthol-3,6-sodium disulfonate undergo substitution reaction, thereby fixing 1-naphthol-3,6-sodium disulfonate on the surface of the bamboo fiber to obtain the reinforcing component.

[0027] 2. Preparation of Inorganic Modified Fillers AA1: Under nitrogen protection, add 2 g of N,N,N',N'-tetramethylethylenediamine to N,N-dimethylformamide, and disperse by ultrasonic for 20 min. Then add 2.8 g of 2,6-dichlorobenzoic acid. After the addition, turn on the heating. After the system temperature reaches 65°C, stir at a constant temperature for 6 h, cool and discharge to obtain the intermediate material. AA2: Ultrasonic disperse 4 g of rectorite with an average particle size of 5 μm in deionized water to form a dispersion, add 3.5 g of the intermediate material to the dispersion, stir at 70°C for 4 h, filter the material, take a solid sample, wash the sample with deionized water, and dry it to obtain an inorganic modified filler.

[0028] The infrared spectrum analysis of inorganic modified fillers was performed using the American Nicolet 170sx Fourier transform infrared spectrometer. Figure 2 As shown by Figure 2 It can be seen that in the infrared spectrum of inorganic modified fillers, 3641cm -1 The characteristic absorption peak of Al-OH appears at 1025cm -1 The characteristic absorption peak of Si-O-Si appears at 3026cm -1 The characteristic absorption peak of the carbon-hydrogen bond in the benzene ring appears at 1760 cm -1 The characteristic absorption peak of the carboxyl group C=O appears at 1405cm -1 The characteristic absorption peak of CN in quaternary ammonium salt appears at .

[0029] Technical principle: In the inorganic modified filler, first, the tertiary amine group in the structure of N,N,N',N'-tetramethylethylenediamine and the halogen functional group in the structure of 2,6-dichlorobenzoic acid undergo continuous quaternization reaction, and the molecular chain continues to extend, eventually forming a polymer containing a large number of quaternary ammonium salts and carboxyl groups in the molecular chain, i.e., the intermediate material; secondly, the cations of the quaternary ammonium salt and the exchangeable cations between the rectorite layers undergo ion exchange reaction, and the intermediate material is inserted into the interlayer of the rectorite to obtain the inorganic modified filler.

[0030] 3. Preparation of environmentally friendly lightweight calcium silicate board (1) 40 g of fly ash, 30 g of cement, 4 g of slaked lime, 8 g of reinforcing component, 5 g of inorganic modified filler and 100 g of water were mixed and stirred at a stirring rate of 600 r / min for 4 h to obtain a mixed slurry; (2) Pour the mixed slurry into the template, and then use a cold press to apply a pressure of 20 MPa for pressing. The pressing process keeps the pressure constant and lasts for 30 minutes to ensure that the slurry is fully solidified. After demolding, the blank plate is obtained; (3) Cut the blank into products of required specifications, pre-curing them in an environment with a pre-curing temperature of 50°C and a humidity of 60% for 10 hours, then place them in a steam curing kettle and cure them at a temperature of 160°C and a pressure of 0.8MP for 8 hours, and then dry them at a temperature of 70°C to obtain an environmentally friendly lightweight calcium silicate board.

[0031] Example 2.

[0032] Preparation of environmentally friendly light calcium silicate board (1) 50 g of fly ash, 40 g of cement, 5 g of slaked lime, 9 g of reinforcing component, 6 g of inorganic modified filler and 150 g of water were mixed and stirred at a stirring rate of 700 r / min for 6 h to obtain a mixed slurry; (2) Pour the mixed slurry into the template, and then use a cold press to apply a pressure of 30 MPa for pressing. The pressing process keeps the pressure constant and lasts for 45 minutes to ensure that the slurry is fully solidified. After demolding, the green plate is obtained; (3) Cut the blank into products of required specifications, pre-curing them in an environment with a pre-curing temperature of 55°C and a humidity of 70% for 15 hours, then place them in a steam curing kettle and cure them at a temperature of 180°C and a pressure of 0.9MP for 10 hours, and then dry them at a temperature of 75°C to obtain an environmentally friendly lightweight calcium silicate board.

[0033] The preparation method of the reinforcing component and the inorganic modified filler is the same as that in Example 1.

[0034] Example 3.

[0035] Preparation of environmentally friendly light calcium silicate board (1) 60 g of fly ash, 50 g of cement, 6 g of slaked lime, 10 g of reinforcing component, 7 g of inorganic modified filler and 200 g of water were mixed and stirred at a stirring rate of 800 r / min for 8 h to obtain a mixed slurry; (2) Pour the mixed slurry into the template, and then use a cold press to apply a pressure of 40 MPa for pressing. The pressing process keeps the pressure constant and lasts for 50 minutes to ensure that the slurry is fully solidified. After demolding, the green plate is obtained; (3) Cut the blank into products of required specifications, pre-curing them in an environment with a pre-curing temperature of 60°C and a humidity of 80% for 20 hours, then place them in a steam curing kettle, cure them at a temperature of 200°C and a pressure of 1MP for 12 hours, and then dry them at a temperature of 80°C to obtain an environmentally friendly lightweight calcium silicate board.

[0036] The preparation method of the reinforcing component and the inorganic modified filler is the same as that in Example 1.

[0037] Comparative example 1.

[0038] Preparation of environmentally friendly light calcium silicate board (1) 50 g of fly ash, 40 g of cement, 5 g of slaked lime, 9 g of reinforcing component and 150 g of water were mixed and stirred at a stirring rate of 700 r / min for 6 h to obtain a mixed slurry; (2) Pour the mixed slurry into the template, and then use a cold press to apply a pressure of 30 MPa for pressing. The pressing process keeps the pressure constant and lasts for 45 minutes to ensure that the slurry is fully solidified. After demolding, the green plate is obtained; (3) Cut the blank into products of required specifications, pre-curing them in an environment with a pre-curing temperature of 55°C and a humidity of 70% for 15 hours, then place them in a steam curing kettle and cure them at a temperature of 180°C and a pressure of 0.9MP for 10 hours, and then dry them at a temperature of 75°C to obtain an environmentally friendly lightweight calcium silicate board.

[0039] The preparation method of the reinforcing component is the same as that in Example 1.

[0040] Comparative example 2.

[0041] Preparation of environmentally friendly light calcium silicate board (1) 50 g of fly ash, 40 g of cement, 5 g of slaked lime, 6 g of inorganic modified filler and 150 g of water were mixed and stirred at a stirring rate of 700 r / min for 6 h to obtain a mixed slurry; (2) Pour the mixed slurry into the template, and then use a cold press to apply a pressure of 30 MPa for pressing. The pressing process keeps the pressure constant and lasts for 45 minutes to ensure that the slurry is fully solidified. After demolding, the green plate is obtained; (3) Cut the blank into products of required specifications, pre-curing them in an environment with a pre-curing temperature of 55°C and a humidity of 70% for 15 hours, then place them in a steam curing kettle and cure them at a temperature of 180°C and a pressure of 0.9MP for 10 hours, and then dry them at a temperature of 75°C to obtain an environmentally friendly lightweight calcium silicate board.

[0042] The preparation method of the inorganic modified filler is the same as that in Example 1.

[0043] Comparative Example 3 Preparation of environmentally friendly light calcium silicate board (1) Mix 50 g of fly ash, 40 g of cement, 5 g of slaked lime and 150 g of water, and stir at a stirring rate of 700 r / min for 6 h to obtain a mixed slurry; (2) Pour the mixed slurry into the template, and then use a cold press to apply a pressure of 30 MPa for pressing. The pressing process keeps the pressure constant and lasts for 45 minutes to ensure that the slurry is fully solidified. After demolding, the green plate is obtained; (3) Cut the blank into products of required specifications, pre-curing them in an environment with a pre-curing temperature of 55°C and a humidity of 70% for 15 hours, then place them in a steam curing kettle and cure them at a temperature of 180°C and a pressure of 0.9MP for 10 hours, and then dry them at a temperature of 75°C to obtain an environmentally friendly lightweight calcium silicate board.

[0044] Performance testing: The environmentally friendly lightweight calcium silicate boards prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 were made into samples that met the specifications. The samples were tested for flexural strength and impact strength according to JC / T 564.1-2018 "Fiber-reinforced calcium silicate boards Part 1: Asbestos-free calcium silicate boards". The specific test results are shown in Table 1: Table 1 - Performance Test

[0045] From the test results in Table 1, it can be seen that the calcium silicate boards prepared in Examples 1 to 3 have excellent strength performance; in the calcium silicate board prepared in Comparative Example 1, only reinforcing components are added. Compared with the examples, the flexural strength and impact strength of the calcium silicate board are slightly reduced, and the strength performance is general; in the calcium silicate board prepared in Comparative Example 2, no reinforcing components are added, and the strength of the calcium silicate board cannot be synergistically improved with the inorganic modified filler, resulting in a further decrease in the strength of the calcium silicate board; in the calcium silicate board prepared in Comparative Example 3, neither reinforcing components nor inorganic modified fillers are added, so the strength performance of the calcium silicate board is the worst.

[0046] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for producing an environmentally friendly lightweight calcium silicate board, characterized in that: The calcium silicate board comprises the following raw materials in parts by weight: 40 to 60 parts of fly ash, 30 to 50 parts of cement, 4 to 6 parts of slaked lime, 8 to 10 parts of reinforcing components, 5 to 7 parts of inorganic modified fillers, and 100 to 200 parts of water; The production method comprises the following steps: (1) Mix fly ash, cement, slaked lime, reinforcing components, inorganic modified fillers and water, and stir at a stirring rate of 600 to 800 r / min for 4 to 8 hours to obtain a mixed slurry; (2) Pour the mixed slurry into the template, and then use a cold press to apply a pressure of 20 to 40 MPa for pressing. The pressing process keeps the pressure constant and lasts for 30 to 50 minutes to ensure that the slurry is fully solidified. After demolding, the blank plate is obtained; (3) Cutting the blank into products of required specifications, and then performing pre-curing, autoclaving and drying treatments to obtain an environmentally friendly lightweight calcium silicate board.

2. The method for producing an environmentally friendly lightweight calcium silicate board according to claim 1, characterized in that: In step (3), the pre-curing process is: pre-curing treatment for 10 to 20 hours in an environment with a pre-curing temperature of 50 to 60° C. and a humidity of 60 to 80%.

3. The method for producing an environmentally friendly lightweight calcium silicate board according to claim 1, characterized in that: The preparation method of the reinforcing component comprises the following steps: A1: placing the bamboo fiber in a potassium hydroxide solution, shaking it for 1 to 2 hours at a temperature of 40 to 50°C and a rotation speed of 100 to 200 r / min, and washing and drying the solution to obtain alkalized bamboo fiber; A2: adding alkalized bamboo fiber and bromoacetic acid to N-methylpyrrolidone, ultrasonicating to form a uniform suspension, adding a catalyst for treatment, raising the system temperature to 105-115°C under stirring conditions, keeping the temperature for 3-5 hours, allowing the material to cool naturally, centrifuging to separate the solid material, washing the solid material, and vacuum drying to obtain modified bamboo fiber; A3: Under the action of the accelerator, the modified bamboo fiber, sodium 1-naphthol-3,6-disulfonate and dimethyl sulfoxide solution are mixed, magnetically stirred evenly, the system temperature is increased to 70-80°C, kept warm and stirred for 4-6 hours, discharged, washed and dried to obtain the reinforcing component.

4. The method for producing an environmentally friendly lightweight calcium silicate board according to claim 3, characterized in that: In step A1, the mass fraction of the potassium hydroxide solution is 10% to 40%.

5. The method for producing an environmentally friendly lightweight calcium silicate board according to claim 3, characterized in that: In step A2, the catalyst is any one of tetraethyl titanate, tetrabutyl titanate or tetraisopropyl titanate.

6. The method for producing an environmentally friendly lightweight calcium silicate board according to claim 3, characterized in that: In step A3, the promoter is any one of sodium carbonate, potassium carbonate or sodium bicarbonate.

7. The method for producing an environmentally friendly lightweight calcium silicate board according to claim 1, characterized in that: The preparation method of the inorganic modified filler comprises the following steps: AA1: Add N,N,N',N'-tetramethylethylenediamine to N,N-dimethylformamide, disperse by ultrasonic for 15-25 minutes, then add chlorine source, turn on heating, wait until the temperature reaches 60-70°C, stir at constant temperature for 4-8 hours, cool and discharge to obtain the intermediate material; AA2: Ultrasonic disperse the rectorite in deionized water to form a dispersion, add the intermediate material to the dispersion, stir for 2 to 6 hours at a temperature of 65 to 75°C, filter the material, take a solid sample, wash the sample with deionized water, and dry it to obtain an inorganic modified filler.

8. The method for producing an environmentally friendly lightweight calcium silicate board according to claim 7, characterized in that: In step AA1, the chlorine source is any one of 2,6-dichlorobenzoic acid or dichloroacetic acid.

9. The method for producing an environmentally friendly lightweight calcium silicate board according to claim 7, characterized in that: In step AA2, the average particle size of the rectorite is 5 μm.

Citation Information

Patent Citations

  • A preparation method of calcium silicate board and calcium silicate board

    CN117263634B

  • Calcium silicate board and preparation method thereof

    CN107473681A

  • Environmentally friendly calcium silicate plate and preparation method thereof

    CN109160798A

  • Lightweight high-strength calcium silicate board and preparation process thereof

    CN109704703A

  • Novel manufacturing and processing technology of calcium silicate board external wall panel

    CN114407168A

Cited By

  • High-strength anti-cracking ceramic and preparation method thereof

    CN120965294A